A widespread family of molecular chaperones promotes the intracellular stability of type VIIb secretion system–exported toxins - Polyniki Gkragkopoulou; Stephen R. Garrett; Prakhar Y. Shah; Dirk W. Grebenc; Timothy A. Klein; Youngchang Kim; John C. Whitney (Proceedings of the National Academy of Sciences, 2025)
To survive in highly competitive environments, bacteria use specialized secretion systems to deliver antibacterial toxins into neighboring cells, thereby inhibiting their growth. In many Gram-positive bacteria, the export of such toxins requires a membrane-bound molecular apparatus known as the type VIIb secretion system (T7SSb). Recently, it was shown that toxin recruitment to the T7SSb requires a physical interaction between a toxin and two or more so-called targeting factors, which harbor key residues required for T7SS-dependent protein export. However, in addition to these targeting factors, some toxins additionally require a protein belonging to the DUF4176 protein family. Here, by examining two toxin–DUF4176 protein pairs, we demonstrate that DUF4176 constitutes a family of toxin-specific molecular chaperones. In addition to being required for toxin stability in producing cells, we find that DUF4176 proteins facilitate toxin export by specifically interacting with a previously uncharacterized intrinsically disordered region found in many T7SS toxins. Using X-ray crystallography, we determine structures of several DUF4176 chaperones in their unbound state, and of a DUF4176 chaperone in complex with the binding site of its cognate toxin. These structures reveal that this binding site consists of a disordered amphipathic α-helix that requires interaction with its cognate chaperone for proper folding. Overall, we have identified a family of secretion system associated molecular chaperones found throughout T7SSb-containing Gram-positive bacteria.